2010
DOI: 10.1590/s0102-311x2010001100009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary assessment in the 1993 Pelotas (Brazil) birth cohort study: comparing energy intake with energy expenditure

Abstract: The study aims to describe and compare two methods of energy intake assessment and one measure of energy expenditure applied in adolescents from a birth cohort. In a sub-sample of the 1993 Pelotas (Brazil) birth cohort, followed up in 2006-7, information on intake was obtained through a food-frequency questionnaire (FFQ) and three 24-hour-recalls (24hR), while energy expenditure was assessed using an accelerometer. Bland & Altman plots were used in the analyses in order to compare the methods. The mean differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A computer-based, semi-quantitative FFQ was developed to be used on the 18th year of follow-up of the 1993 Pelotas Birth Cohort (13) based on the paper version of a validated Brazilian FFQ (14) , adapted to the cohort after carrying out a sub-study when the participants were 15 years of age. That previous study has been reported elsewhere (15) . The electronic platform comprises all the food items included in the paper version of the FFQ (15) .…”
Section: Semi-quantitative Ffqmentioning
confidence: 51%
“…A computer-based, semi-quantitative FFQ was developed to be used on the 18th year of follow-up of the 1993 Pelotas Birth Cohort (13) based on the paper version of a validated Brazilian FFQ (14) , adapted to the cohort after carrying out a sub-study when the participants were 15 years of age. That previous study has been reported elsewhere (15) . The electronic platform comprises all the food items included in the paper version of the FFQ (15) .…”
Section: Semi-quantitative Ffqmentioning
confidence: 51%
“…Even though, results should be interpreted with caution. The administered FFQ was developed for the follow-up at age 15 of the 1993 Birth Cohort [ 23 ] and was based on a validated FFQ [ 24 ], but it was not validated for the follow-up at age 18. We cannot rule out the possibility of misreporting of food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…For each food item, the participant was first asked about the frequency of intake and for those reported items the platform presents photographed images to identify the usual portion size (small, medium, or large). This electronic platform was developed to be used on the 18th year of follow up of the 1993 Pelotas Birth Cohort, and was based on a recent validation (paper-based FFQ) carried out when subjects from the 1993 Pelotas birth cohort were 15 years [ 23 ]. The electronic platform comprises all the food items included in the paper version of the FFQ [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain the data regarding the quantities consumed, a mean serving for each food was defined, considering that the respondent should inform whether having consumed each time an equal, larger, or smaller amount in relation to the mean serving. In order to define the mean serving, the data from three 24HR was applied in a substudy conducted in 2006 15 with 185 adolescents in the cohort of 1993, aged 13 years at the time. Some foods were grouped by type and nutritional composition (e.g., crystal sugar and refined sugar were classified as sugar).…”
Section: Development Of the Self-administered Digital Ffqmentioning
confidence: 99%